Progressive Scrutiny: Incremental Detection of UBI bugs in the Linux Kernel - Zhai, Yizhuo; Hao, Yu; Zhang, Zheng; Chen, Weiteng; Li, Guoren; Qian, Zhiyun; Song, Chengyu; Sridharan, Manu; , Srikanth V. Krishnamurthy; Jaeger, Trent; Yu, Paul (Network and Distributed Systems Security (NDSS) Symposium 2022, 2022)
The Linux kernel has a rapid development cycle, with 10 commits every hour, on average. While these updates provide new features and bug fixes, they can also introduce new bugs and security vulnerabilities. Recent techniques showed how to detect some types of vulnerabilities using static analysis, but these tools cannot run quickly enough to keep up with the pace of kernel development. Ideally, an incremental analysis technique could address this problem, by doing a complete analysis once and then only analyzing changed portions of the code subsequently. However, incremental analysis of the Linux kernel poses unique challenges, due to its enormous scale and the high precision required to reduce false positives. In this paper, we design and implement INCRELUX, a novel Linux kernel incremental analysis tool. It allows rapid vulnerability detection after each update, via targeted analysis of the new code and affected prior code, and also speeds the tracking of pre-existing bugs to understand how long they have been present, thereby increasing awareness of such bugs. Our approach hinges on a bottom-up, function-summary-based approach, which leverages the benefits of a one-time clean-slate, but expensive analysis of a prior Linux baseline. INCRELUX also uses an effective heuristic to apply symbolic execution to incremental results to improve precision. Via extensive experiments on the challenging problem of finding use-before-initialization (UBI) bugs, we showcase a number of benefits of INCRELUX:(a) we can rapidly check if any new releases introduce UBI bugs and help eliminate them early in the process. (b) we perform a …